KOMPARATIF ANALISIS PEMIKIRAN EPISTEMOLOGI IBNU SINA DAN MULLA SADRA: IMPLIKASINYA TERHADAP PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM DI ERA MODERN - Muhammad Ruhul Islam; Azka Ilma Zhafirah; Imron Rossidy; Muhammad Inam Esha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study conducts a comparative analysis of the epistemological thought of Ibn Sina and Mulla Sadra and examines its implications for the development of Islamic education curricula in the contemporary era, given that the intellectual contributions of both scholars remain highly relevant to ongoing educational discourse. Using a library research method with a qualitative-descriptive approach and comparative analysis of relevant literature, the study finds that Ibn Sina’s epistemology emphasizes the integration of sensory experience, rational reasoning, and intuitive insight, with demonstrative reasoning and intellect serving as the primary tools for attaining truth, whereas Mulla Sadra, through the framework of al-Hikmah al-Muta‘aliyah (Transcendent Philosophy), constructs an epistemological system that unites reason, revelation, intuition, and spiritual experience within an existential and transformative understanding of knowledge. Although both philosophers acknowledge the importance of intellect and metaphysical dimensions, they differ in their conceptualization of knowledge and the relationship between the knower and the known. Their epistemological perspectives collectively offer significant implications for curriculum development that bridges religious and secular sciences, harmonizes rationality and spirituality, and integrates theoretical understanding with practical application and character formation, thereby enabling Islamic education to produce learners who are intellectually competent, ethically grounded, spiritually mature, and capable of navigating modern challenges without losing their Islamic identity.